2013
DOI: 10.1021/es303586x
|View full text |Cite
|
Sign up to set email alerts
|

Abatement of an Aircraft Exhaust Plume Using Aerodynamic Baffles

Abstract: The exhaust jet from a departing commercial aircraft will eventually rise buoyantly away from the ground; given the high thrust/power (i.e., momentum/buoyancy) ratio of modern aero-engines, however, this is a slow process, perhaps requiring ∼ 1 min or more. Supported by theoretical and wind tunnel modeling, we have experimented with an array of aerodynamic baffles on the surface behind a set of turbofan engines of 124 kN thrust. Lidar and point sampler measurements show that, as long as the intervention takes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Emissions are subject not only to transport processes in the environment atmosphere, but also to those associated with the aircraft itself. Exhausts from engines have a release momentum and acquire a vertical momentum as a result of their buoyancy, and may reside within a wake as result of the lift and drag on the airframe (Bennett et al, 2010(Bennett et al, , 2013. Since the emission time step is an hour long, engine thrust have been neglected; the plume rise has been accounted for but it is not discussed in this paper, as it will be further explained in another section.…”
Section: Emission Sourcesmentioning
confidence: 99%
“…Emissions are subject not only to transport processes in the environment atmosphere, but also to those associated with the aircraft itself. Exhausts from engines have a release momentum and acquire a vertical momentum as a result of their buoyancy, and may reside within a wake as result of the lift and drag on the airframe (Bennett et al, 2010(Bennett et al, , 2013. Since the emission time step is an hour long, engine thrust have been neglected; the plume rise has been accounted for but it is not discussed in this paper, as it will be further explained in another section.…”
Section: Emission Sourcesmentioning
confidence: 99%
“…In their simplest form, appropriately angled and placed baffles may have the potential to instantly reduce exposure and consequent ill-health outcomes whilst being rapidly retrofittable to existing walls. Similar baffle structures have been demonstrated as effective in the horizontal plane around airports (Bennett et al 2013) and topological shaping has been recommended to attenuate sound (Dühring et al 2008).…”
Section: Introductionmentioning
confidence: 91%
“…It is found that the wind direction angle that has the most effect on the deflection of jet blast is lower than ninety degrees. Supported by theoretical and wind tunnel modeling, Bennett et al [9] have experimented with an array of aerodynamic baffles on the surface behind a set of turbofan engines of 124 kN thrust. Lidar and point sampler measurements show that, as long as the intervention takes place within the zone where the Coanda effect holds the jet to the surface (i.e., within about 70 m in this case), quite modest surface-mounted baffles can rapidly lift the jet away from the ground.…”
Section: Introductionmentioning
confidence: 99%